Palladium-Catalyzed Carbonylative Homocoupling of 2-Iodophenols for the Synthesis of Symmetrical Xanthones - Lokolkar, Manjunath S.; Bhanage, Bhalchandra M. (Synlett, 2023)
Herein, we report the palladium-catalyzed carbonylative synthesis of symmetrical xanthones from functionalized 2-iodophenols in a one-pot manner. The protocol involves homocoupling of 2-iodophenols using Pd catalyst, Cs2CO3 as base, with gaseous CO as C1 building block. The simple, ligand- and additive-free strategy provides moderate to good yields of symmetrical xanthones. The reaction was also examined with the combination of 2-hydroxyphenyl boronic acid as another coupling partner. Additionally, this protocol was extended for the synthesis of aryl and alkyl salicylate derivatives by varying the reaction conditions.
Keywords: carbonylation; homocoupling; palladium; xanthones; 2-iodophenols